El Greco's achievement of his personal maniera - Maré, Estelle Alma (University of the Free State, 2002)
Domenicos Theotocopoulos, generally known as El Greco, was born in Crete in 1541. Before he left his native island he was a competent, late Byzantine painter. In his late twenties, he went to Venice, where he learnt the craft of Western painting, most probably in Titian's workshop. He left Venice in 1570 and became an independent painter in Rome before departing for Spain in 1576, where he may have sought the patronage of Phi lip II, from whom he initially received commissions. After a brief stay in Madrid, he took up residence in Toledo where he practised as a religious painter in the service of the post- Tridentine Roman Catholic Church, and produced his most distinctive paintings in a manner that is unique in the Renaissance tradition. The purpose of this dissertation is to explore how El Greco achieved his personal manner of expression or maniera and, more specifically, what this very distinct, personal manner of expression or ultima maniera entailed. Part I (Chapter 1) is an overview of the life of the artist and the contexts in which he acquired his knowledge of ltalian Renaissance artistic practice and his painterly skills. Part II deals with the general ideas and ideals that informed Italian Renaissance art (Chapter 2), and then goes on to focus on those aspects which specifically informed El Greco's apprenticeship in the Western painterly tradition (Chapter 3), as well as his own ideas on the art of painting. To arrive at an evaluation of the development of his personal manner of expression, the Part III is devoted to the analysis of selected paintings executed in Venice and Rome in which the characteristics of his later manner of expression are already in evidence (Chapter 4). A further chapter (5) is devoted to two important works painted during his early years in Toledo in which his manner of expression, although reminiscent of the forms favoured by Italian Mannerist painters, is already uniquely transformed into a personal vision. The main focus of the dissertation is chapter 6 of Part IV which contains an analysis of the angelic figures which are so predominant in El Greco's oeuvre. The selected paintings are dealt with under nine sub-headings in which the actions of the depicted angels are broadly categorised. The analyses focus on the distinctive forms of the angelic figures, their interaction with other figures and the meanings that the compositions acquire through the way in which they are represented. In this regard, some of El Greco's most renowned paintings, such as the Burial of the Count of Orgaz and two versions of the Baptism of Christ, are reinterpreted and re-evaluated. While he does not deviate radically from traditional iconography in the representation of most of his themes, El Greco's most innovative contribution to sixteenth-century painting is the expansion and transformation of the formal qualities he derived from Mannerism. With increasing skill he infused angelic and many human figures with movement by turning them into open-ended, elongated spiral forms, and creating the verticality characteristic of his compositions. This manner of representation acquires a symbolic meaning in which religious and artistic concerns are unified. As such, El Greco's angelic figures exemplify a key element of his manner of expression and artistic vision. They become metafigures, as stated in the concluding chapter which summarizes the characteristics of his ultima maniera.

Domenicos Theotocopoulos, algemeen bekend as El Greco, is in 1541 in Kreta gebore. Voordat hy sy geboorteplek verlaat het, was hy 'n bekwame laat-Bisantynse skilder. In sy laat twintigerjare het hy na Venesië vertrek waar hy die vaardighede van 'n Westerse skilder aangeleer het, hoogs waarskynlik in Tiziano se ateljee. Hy het Venesië in 1570 verlaat en 'n onafhanklike skilder in Rome geword voordat hy in 1576 na Spanje vertrek het, waar hy waarskynlik die beskermheerskap van Philipus II wou bekom en van wie hy aanvanklik opdragte ontvang het. Na 'n kort verblyf in Madrid het hy hom in Toledo gevestig waar hy gepraktiseer het as 'n religieuse skilder in die diens van die Rooms-Katolieke Kerk in die tydperk na die Konsilie van Trente en het aldaar sy mees kenmerkende skilderye voortgebring op 'n wyse wat uniek is in die Renaissance-tradisie. Die doel met hierdie verhandeling is om insig te verkry in hoe El Greco sy persoonlike wyse van uitdrukking of maniera verwesenlik het, en meer spesifiek, wat sy hoogs uitkenbare, persoonlike wyse van uitdrukking of ultima maniera behels het. In die eerste deel word 'n oorsig gegee van die lewe van die kunstenaar en die konstekse waarin hy sy kennis van die kunspraktyk van die Italiaanse Renaissance en sy skildervaardighede bekom het. Die tweede deel handeloor die algemene idees wat in Italiaanse Renaissance-kuns uitgedruk is, met meer uitvoerige besprekings van daardie aspekte wat spesifiek op sy leerlingskap in die Westerse tradisie betrekking gehad het, asook sy eie idees oor die skilderkuns. Ten einde die ontwikkeling van sy persoonlike wyse van uitdrukking te kan evalueer, word die derde deel gewy aan ontledings van gekose skilderye wat in Venesië en Rome uitgevoer is en waarin die kenmerke van sy latere wyse reeds opmerkbaar is. Die volgende hoofstuk word gewy aan twee belangrike skilderye wat tydens sy vroeë jare in Toledo uitgevoer is, waarin die wyse van uitdrukking, hoewel dit die vorms wat deur Italiaanse maniëristiese skilders in die gedagte roep, reeds op 'n unieke wyse in 'n persoonlike visie getransformeer is. Die belangrikste fokus van die dissertasie is hoofstuk 7 waarin 'n ontleding gedoen word van engelfigure as 'n spesifieke tema in El Greco se oeuvre. Die gekose skilderye word onder nege sub-opskrifte behandel waarin die handelinge van die afgebeelde engele breedweg gekategoriseer word. Die ontledings fokus op die kenmerkende vorms van die engelfigure, hulle interaksie met ander figure en die invloed daarvan op die betekenis van die komposisies as geheel. In hierdie verband word etlike van El Greco se beroemdste skilderye soos die Begrafnis van die hertog van Orgaz en twee weergawes van die Doop van Christus geherinterpreteer en geherevalueer. Terwyl hy nie radikaal afwyk van tradisionele ikonografie in die voorstelling van die meeste van sy temas nie, is El Greco se mees innoverende bydrae tot die sestiende-eeuse skilderkuns die uitbreiding en transformasie van die formele kwaliteite wat hy uit die Maniërisme oorgeneem het. Met toenemende vaardigheid het hy engel- en ook vele mensfigure deur beweging geaktiveer deur hulle in oop, verlengde spiraalvorme te transformeer, met 'n gevolglike toename in vertikaliteit in sy komposisies. Hierdie wyse van uitdrukking het 'n simboliese betekenis verkry waarin die belange van godsdiens en kuns verenig is. As sodanig is die engelfigure draers van 'n hoogs belangrike aspek van El Greco se wyse van uitdrukking en artistieke visie.
Thesis (Ph.D. (History of Art and Visual Culture Studies))--University of the Free State, 2002
Keywords: Dissertation; Painting, Spanish; Mannerism (Art) -- Spain; Greco, 541?-1614 -- Criticism and interpretation